Mineralization of iron oxide by ferritin homopolymers immobilized on SiO2 nanoparticles. Issue 1 (8th January 2019) - Carmona, Daniel; Treccani, Laura; Michaelis, Monika; Lid, Steffen; Debus, Christian; Ciacchi, Lucio Colombi; Rezwan, Kurosch; Maas, Michael
Abstract : The iron storage protein ferritin is well known for its ability to mineralize iron oxides in its interior cavity. In this study, the authors investigated the mineralization behavior of H and L ferritin homopolymers assembled from individual subunits. The authors' approach included molecular dynamics simulations, which suggested that ferritin subunits arrange themselves on silica surfaces with the active side facing away from the interface, although non covalent adsorption interactions might be weak. In experimental studies, the nucleation of iron oxide nuclei could be observed at ferritin homopolymers which were covalently immobilized through the EDC/NHS strategy at the surface of silica nanoparticles. Mineralization was initiated by the addition of ammonium iron (II) sulfate hexahydrate ((NH4 )2 Fe(SO4 )2 ·6H2 O) as the source of iron ions and trimethylamine N -oxide as the oxidant. The results demonstrate that immobilized H and L ferritin homopolymers on silica surfaces are able to induce the formation of a cohesive thin film of magnetic iron oxide crystals (magnetite and/or maghemite).